Aklimatisasi Planlet Pisang Varietas Raja Bulu Kuning Berbasis Sistem Hidroponik Substrat - Endang Setia Muliawati; Retna Bandriyati Arniputri; Nandariyah Nandariyah; Sidik Nur Cahyo Utomo (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Banana is one of the favorite tropical fruit. Banana business development begins with the provision of quality seeds. Tissue culture is a seed propagation technology that can produce large amounts of seed and a relatively short time by utilizing limited plant material. The planlets result of tissue culture needs to be acclimatization before planted in the field. Hydroponic substrate-based acclimatization is expected to produce seeds that are free from soil pathogens. Adjustment of the concentration of nutrients is important in order to produce a growth response that significantly affects and does not cause poisoning or plasmolysis. This study aims to determine whether hydroponic substrate types and nutrient concentrations affect the growth of Raja Bulu Kuning Banana plantlets. The experiment was carried out at net house, Faculty of Agriculture, Universitas Sebelas Maret Surakarta in October 2016 - January 2017. The treatment factors were substrate types (bagasse, arenga peat, steamed husk) and concentration of the nutrient solution (equivalent to EC 1.8, EC 2.0, and EC 2.5 mScm-1). The result showed that steamed husk is the best as the hydroponic substrate, while nutrient solution concentration equivalent to EC 1.8 mScm-1 is sufficient for acclimatization of Banana plantlets cv.Raja Bulu Kuning.